Development of an e-module based on the Self-Organized Learning Environment (SOLE) model assisted by Artificial Intelligence (AI) on kinematics material - Anggraini, Welly; Komikesari, H.; Pratiwi, Mala; Ningtias, Putri Ayu (Universitas Muhammadiyah Mataram, 2024)
This development research aims to develop an e-module based on the Self-Organized Learning Environment (SOLE) model assisted by Artificial Intelligence (AI) on kinematics material. The research and development method uses the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) approach created by Robert and Maribe Brach. This model includes the following stages: 1) Analysis, 2) Design, 3) Development, 4) Implementation, 5) Evaluation. The subjects of this research were students from two schools, and the data collection instruments were questionnaires provided to expert validators and students. The data generated is qualitative and analyzed using assessment criteria guidelines to determine the quality of the product. The results of this research produced teaching materials and determined the quality of the developed product: 86% from material experts (categorized as highly feasible), 95% from media experts (categorized as highly feasible), 87% from educators, and 93% from students in small-scale trials, with 87% in large-scale trials, all categorized as very attractive. Based on these results, it can be concluded that the E-module based on the Self-Organized Learning Environment (SOLE) model assisted by Artificial Intelligence (AI) for kinematics material is highly feasible and attractive for use in high school physics learning for 11th-grade students.